Determination of factors influencing consumption pattern of ghee in Bengaluru market: An application of logistic regression analysis - Sivaram, Muniandy (Indian Journal of Dairy Science, 2016)
Ghee is a highly priced dairy product of Indian sub- continent, prepared by clarification of cow/buffalo/ mixed milk fat. In this study, an attempt was made to determine the factors influencing the consumption pattern of ghee in Bengaluru district of Karnataka State, India.Â For this purpose, the data from three hundred sample respondents was collected using multistage stratified random sampling technique. Of the 255 respondents who consumed ghee, 32.5% consumed every day while 30.8% consumed on certain days. The monthly per capita expenditure on ghee was ` 33.88 which is 2.1% of the total monthly per capita expenditure. The consumption frequency of ghee and monthly per capita expenditure on ghee per month were found to have significant association with family size and food habit.Â Of the 19 brands of ghee indicated by the respondents, the major brands were Nandini and GRB. The logistic regression analysis revealed that the preference for Nandini brand were influenced by family size, age of the respondents, expenditure on consumption of ghee, total years of ghee consumption, flavour and shelf-life of ghee. The variables that were found to significantly influence the preference for GRB are expenditure on consumptions of ghee and years of consumption. The analysis revealed that there was a brand loyalty for Nandini by the consumers. The economical retail price of Nandini was also seen as a major factor for its preference. The preference for GRB was seen among the new generation consumers and with higher income groups.